Comprehensive evaluation on product characteristics of fast hydrothermal liquefaction of sewage sludge at different temperatures. (15th September 2018) - Xu, Donghai; Lin, Guike; Liu, Liang; Wang, Yang; Jing, Zefeng; Wang, Shuzhong
Abstract: Hydrothermal liquefaction (HTL) can chemically convert sewage sludge (SS) into a crude bio-oil (biocrude) and other by-products. This work systematically elucidates how the yields and compositions of different products (e.g., gases, biocrude and solids) vary with temperature (260–350 °C) in SS HTL with 10 min of residence time. The results show that increasing temperature improved the biocrude quality and the gas yield, declined the water-soluble substance yield, the solid yield, and the TOC (total organic carbon) content in aqueous phase, while the biocrude yield and the NH3 -N (ammonia nitrogen) content in the aqueous phase first raised and then decreased, and reached the maximum values at 340 °C. After SS HTL at 340 °C, light biocrude, light solids, water-soluble organic matters accounted for about 54.4, 50.5, 88.9 wt% of total biocrude, solids and water-soluble substances, respectively. The N and S contents in the light biocrude almost halved compared with those in the heavy biocrude. The light solids contained a higher C content but lower Al, Si, Ca and Fe contents than did the heavy solids. >93.0 wt% of Cu, Zn and Cr remained in the solids in contrast to 0.5–1.0 wt% in the aqueous phase and 0.2–4.7 wt% in the biocrude. Highlights: Change trends of product properties with temperature in fast SS HTL were shown. The highest biocrude yield and energy recovery were gained at 340 °C in SS HTL. Arsenic was almost partitioned averagely in solids, aqueous phase and biocrude. Light biocrude accounted for 54.4 wt% of total biocrude after SS HTL at 340 °C. Light solids occupied 50.5 wt% of total solids after SS HTL at 340 °C.